2018
DOI: 10.1002/jcp.26799
|View full text |Cite
|
Sign up to set email alerts
|

Excessive training induces molecular signs of pathologic cardiac hypertrophy

Abstract: Chronic exercise induces cardiac remodeling that promotes left ventricular hypertrophy and cardiac functional improvement, which are mediated by the mammalian or the mechanistic target of rapamycin (mTOR) as well as by the androgen and glucocorticoid receptors (GRs). However, pathological conditions (i.e., chronic heart failure, hypertension, and aortic stenosis, etc.) also induce cardiac hypertrophy, but with detrimental function, high levels of proinflammatory cytokines and myostatin, elevated fibrosis, redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 41 publications
3
21
0
3
Order By: Relevance
“…This study showed that overtraining increased the TNF-α level and tended to increase the IL-6 level in the heart, consistent with other studies [4,15,16]. Overtraining has been proved to induce acute local inflammation, which may develop into chronic inflammation, thus producing systemic inflammation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This study showed that overtraining increased the TNF-α level and tended to increase the IL-6 level in the heart, consistent with other studies [4,15,16]. Overtraining has been proved to induce acute local inflammation, which may develop into chronic inflammation, thus producing systemic inflammation.…”
Section: Discussionsupporting
confidence: 91%
“…The symptoms of OTS are varied, and they include fatigue, depression, bradycardia, loss of motivation, insomnia, irritability, agitation, tachycardia, hypertension, restlessness, anorexia, weight loss, lack of mental concentration, stiff muscles, anxiety, and awakening unrefreshed [3]. In mice, OTS led to left ventricular hypertrophy and increased gene expression related to pathological hypertrophy, such as mRNA for the ANP, mRNA for β-myosin heavy chain, and mRNA for skeletal muscle actin [4].…”
Section: Introductionmentioning
confidence: 99%
“…For example, it was reported that 16 weeks of habitual voluntary wheel running had no effects on myocardial collagen concentration and cross-linking in the rat left ventricle, although cardiac stiffness was reduced (Woodiwiss, Oosthuyse, & Norton, 1998). We speculate that the mild enhancement of collagen I expression represents an adaptive response of heart to exercise stress as recently reported by da Rocha et al (2018) and is substantially different from the robust increase of collagen I expression following MI, which led to pathologic fibrosis in the heart (Figure 3). In fact, another study showed that exercise training prevented the decline in mRNA of collagen I and III in middle-aged rats and attenuated the decline in senescent animals (Thomas, Zimmerman, Hansen, Martin, & McCormick, 2000).…”
Section: Discussionsupporting
confidence: 65%
“…Under the physiological condition, the cardiac function can be performed in an orderly manner [ 93 ]. However, if it exceeds the range of compensation owing to cardiac pressure or volume overload, such as high levels of angiotensin II (AII), chronic hypertension, valvular dysfunction, myocardial infarction, and even excessive training, the hypertrophy shifts to an irreversible pathology, which induces severe arrhythmia or cardiac failure [ 22 , 103 , 104 , 105 , 106 ].…”
Section: Trpm4 and Cardiovascular Diseasementioning
confidence: 99%